An analysis of the mathematics school examination test quality - Hadi Sutrisno (Jurnal Riset Pendidikan Matematika, 2016)
This research aims to describe: (1) the quality of mathematics school examination test of the Junior High School for the academic year 2015/2016 in Kabupaten Bangkalan based on qualitative analysis of tests item, (2) ) the quality of mathematics school examination test of Junior High School for the academic year 2015/2016 in Kabupaten Bangkalan based on quantitative analysis of test items, and (3) the test equating on mathematics school examination test for the academic year of 2015/2016 of Junior High School in Kabupaten Bangkalan. A test is said to be quality if it fulfills validity, reliability, and it has good characteristic. A test is said to be equivalent to another if the test scores of one test can be exchanged with the scores of another test. The data is taken from school examination script accompanied with the answer sheets of students. Qualitative data analysis was conducted with the help of experts judgement. Quantitative data analysis was conducted with Classical Test Theory by Iteman and Item Response Theory by BilogMG. These programs are used to find out the test quality quantitatively. In order to analyze the equivalence between series of tests, item-characteristic curves were used. These curves were drawn by Geogebra. The research result shows: (1) qualitatively, the test plan quality of mathematics school examination test is quite good. Meanwhile, the school exam quality is quite good and not so good, (2) quantitatively, the school examination test quality is good, and (3) equating, based on the item-characteristic curves, the school examination tests is equal.